Clone Detection Using Abstract Syntax Trees - Sridevi, L; Kannan, R (International Journal of Computer Sciences and Engineering, 2025)
Clones are the piece of Software, which is creating from the copy of the original software. To be more specific, the idea behind software cloning is to create a new software that replicates the aspect and usefulness of the original software in possible. It is important to understand that cloning does not have to involve any source code in the original software. Software Cloning typically occurs in the source code for the original software is not available. In a result, software cloning does not imply source code copying. Since software cloning goes way beyond simply executing a similar user interface. The goal in cloning is to create a new software program that mimics everything the original software does and the way in which it does.